La responsabilidad civil por los efectos secundarios de la vacuna contra la COVID-19. - Haro Olivo, Evelin Yajaira (2023)
Vaccination against COVID-19 was born as the only primary prevention tool to limit the health and economic impact of the pandemic. The objective of the vaccine against COVID-19 is to care for the population by reducing mortality caused by the disease and avoiding the collapse of health systems, and being able to maintain their capacity to meet the health needs of the population without considering the effects that they could produce in the future due to their rapid manufacturing. Regarding Ecuadorian legal legislation, it does not cover any vaccine manufacturing process, nor is there any specific legislation regarding the civil liability of the Ecuadorian State for possible medical effects of vaccines in general. Due to the above, Ecuadorians are defenseless in the national legal sphere since we could hardly find a real cause to initiate compensation due to the effects of the COVID-19 vaccine. The only international vaccine injury compensation program offers eligible individuals in the Metropolitan Control Agency-AMC eligible countries and economies a fast, fair, robust, and transparent process to be repaid for rare but serious adverse events related to vaccines distributed by Vaccines Global Access/Vacunas de Acceso Global-COVAX. In the present study, surveys were collected, in addition to carrying out a detailed investigation on national legislation and verifying that there is no clear legislation that allows compensation to possible victims of the affectations, at the international level, the COVAX program of the World Organization for Health-WHO through which it is intended to compensate people who have effects due to vaccination to mitigate COVID-19.